Aplicación de la teoría de Katharine Kolcaba en el cuidado de enfermería al paciente Hemodialítico - Luz María Lalón Ramos (2021)
ABSTRACT Hemodialysis is an extracorporeal blood purification technique. According to data obtained by the Ministerio de Salud Pública from 2015 to 2017, around 3,102 users were undergoing renal replacement therapy. Who in turn may present behaviors that alter their quality of life such as: stress, social isolation, insecurity, dependence and fear, having an impact on adherence to treatment. The general objective is to identify the application of Katharine Kolcaba's theory in nursing care for hemodialysis patients. The 95 bibliographic sources from different databases were reviewed and after applying inclusion and exclusion criteria, a sample of 70 bibliographic sources was obtained, of which 30 were used for the triangulation process. Based on the results, interventions were determined through four contexts: physical, environmental, social and spiritual mentioned in Kolcaba's theory, but not a feeling of relief, tranquility and transcendence. NANDA diagnostic labels were proposed, which will allow greater expression of emotions, experiences and expectations of quality of life. Key words: hemodialysis, comfort contexts, Nursing Care. Firmado electrónicamente por: DIANA CAROLINA CHAVEZ GUZMAN Reviewed by: Lcda. Diana Chávez ENGLISH PROFESSOR C.C. 065003795-5